La influencia del latín en la puntuación de Nebrija - Pawlak, Aneta (Rome and Iberia : Inspirations and Connections throughout History, 2021)
The purpose of the paper is to expose the influence that Latin had on the punctuation system used by Antonio de Nebrija, both in his works written in Latin and those in Spanish. First, an outline is drawn of the evolution of punctuation from Antiquity to the Middle Ages; then, the punctuation used in the three editions of Nebrija’s paragraph De punctis clausularum is compared. Finally, the main conclusions are summarized, including the need to increase and modify the binary system considered by Nebrija as a role model.